MEMBINA RELASI DAMAI ANTARA MAYORITAS DAN MINORITAS (Telaah Kritis atas Peran Negara dan Umat Islam dalam Mengembangkan Demokrasi di Indonesia) - Suprapto, Suprapto (Analisis: Jurnal Studi Keislaman, 2012)
Indonesia  is  considered  the  most  populous  Muslim  country  in  the world that successfully develops democracy. In one hand or another, however,  a number  of ill treatments  of discrimination  over those of minorities in this country   continuously remains occurring. The minorities have not been fully acquired their rights mainly in relation to religious  freedom.  This  article  tries  to map  out the relationship between majority Muslims and non-Muslim  minorities  in Indonesia, which involves two important issues: Readiness of majority culture as the main subject and state constitution. Various human rights violations and  discrimination  experienced  by  minorities  was  not  solely  done by a mere majority, but also by state. It, has systematically  issued a potential number of legislation products which marginalizes minorities and favored majority.   To protect the rights of citizens from majority groups  and   state interference,  this article  puts forward  two steps; political advocacy of equality and capacity building for strengthening democratic  values. The first step is intended to encourage  the more serious attention  to and protect the existence  of minority  groups by issuing laws and regulations  that are fair and protected all citizens. While the second step is needed to strengthen democratic values such as liberty, equality and tolerance that has existed within the majority, those of Indonesian Muslims.